Assessment of the Color Stability of Clear Elastomeric Ligatures (An In Vivo Study) - Shams Kadhum; Alhuwaizi, Akram Faisal (Journal of Baghdad College of Dentistry, 2017)
Background: The desire for an attractive appearing fixed orthodontic appliance fueled the use of ceramic brackets and clear accessories. Elastics are one of the most versatile materials available to orthodontists so studying their effect on the esthetic appearance is important. This an in vivo study, conducted to evaluate the effect of exposing stretched clear elastomeric ligatures to the oral environment from four different companies (OrthoTechnology, Morelli, Ortho Organizer, and Ormco). Materials and Methods: A total of 240 elastomeric modules were examined, 60 modules from each brand. Each of the 60 patients enrolled in the study, received 4 elastomeric modules on the 4 lower incisors, one from each brand. The specimens were placed on the teeth for 1, 2 and 4 weeks. After removal each module was kept in a sealed plastic bag and prepared for imaging and color measurement. Color measurements were made before and after use of the specimens. Images were taken by a cellular attachable microscope connected to a mobile phone with special J-cam program and the color change was calculated according to CIE Labcolor spaces system by the Adobe Photoshop program. The resulting data were statistically analyzed using ANOVA, LSD and Chi square tests. Results: The results showed that, all the elastomeric ligatures discolored after use. The discoloration increased with an increased incubation period in the mouth reaching the peak at 4 weeks interval and the yellowness index was the mostly effected color component. Elastomeric ligatures from Morelli brand were the most prone to discoloration, while Ortho Organizers and Ormco ligatures were the least prone to discoloration with the presence of large individual variation. Conclusion: It is necessary to alert the patient about the color changes that the clear ligatures experienced and the staining effect of certain foods. The orthodontist should select brands that are more resistant to color changes.